Synergizing airborne Hyperspectral Imaging and ground truth data for environmental monitoring: Insights from the CERAD campaign - Mettas, Christodoulos; Themistocleous, Kyriacos; Prodromou, Maria; Kountouri, Josefine; Kalogirou, Eleftheria; Evagorou, Evagoras S.; Tzouvaras, Marios; Christoforou, Michalakis; Loulli, Eleni; Charalampous, Georgia; Eliades, Marinos; Pittaki, Zampella; et al. (My University, 2024)
This work presents the Cyprus Flight Campaign of ERATOSTHENES Centre of Excellence and DLR (CERAD) that took place in October 2023 within the framework of the EXCELSIOR H2020 Widespread Teaming Phase 2 project titled "ERATOSTHENES: EXcellence Research Centre for Earth SurveiLlance and Space-Based Monitoring of the EnviRonment". The campaign's main goal was to acquire about 100.000 high-resolution stereo 3K images and hyperspectral HySpex images, complemented by ground truth measurements to perform high-resolution hyperspectral analysis and 3D mapping. The campaign aimed at the capacity development of ERATOSTHENES Centre of Excellence staff on processing these imagery, cross-calibration and validation of sensors, and analysis of land, water, and cultural heritage sites with hyperspectral sensors. This campaign captured high-resolution hyperspectral imagery across a wide spectral range (420-2500nm) in several parts of Cyprus (Paphos and Limassol Districts). Parallel to this airborne campaign, the research team of ERATOSTHENES Centre of Excellence conducted a ground-based measurement campaign, which included the collection of spectroradiometric measurements (HR 1024 and GER 1500), water samples for laboratory analysis of water (e.g., dissolved organic matter) and soil (e.g., texture, pH, organic content) samples, GPS tracking, soil moisture and meteorological sensors and on-board UAV multispectral cameras. The collected data will support various applications, such as calibration and validation of satellite products, environmental monitoring, vegetation analysis, and disaster risk assessment. According to the literature, the use of airborne hyperspectral imaging is essential since the airborne remote sensing data acts as a bridge between large-scale satellite and point-scale field observations. Furthermore, hyperspectral imaging is a simultaneous acquisition of spatial images in several spectrally adjacent bands and a highly multidisciplinary and complex field. The present campaign demonstrates the efficiency of airborne hyperspectral imaging in capturing detailed environmental data and highlights the vital role of ground-truth measurements in verifying airborne and enriching environmental data. The combined use of the methods mentioned above paves the way for advanced ecological monitoring thereby contributing to informed decision-making and sustainable development efforts.
Keywords: Hyperspectral imaging; Sensors; Environmental monitoring; Environmental sensing; RGB color model; Agriculture; Remote sensing